Implementasi Decision Tree pada Social Network - Yunda Heningtyas (Politeknik Negeri Lhokseumawe, 2017)
The strategy of business today is no longer done traditionally. By the presence of internet, marketing strategies can be done with the wider reach. Viral marketing is a new program in an electronic format that was created to assist in the marketing of products by making the consumer as an object to spread the advertising of a product. Abundant data from the social network has the potential information that can be utilized for virtual marketing. Social network analysis using a decision tree will produce a potential users and a pattern that could affect the user is to distribute advertising the product. Result is rules that contains the attributes which can influence the pattern indicate users to execute of the strategy business of viral marketing